Systemic functional linguistics and discourse analysis as alternatives when dealing with texts (2014)
This article presents a case study research with aims to find out which activities, methodological and textual aspects used in a reading strategies course were causing a group of students difficulties when analyzing critically written information. We conducted the study at Universidad de Córdoba (Colombia) with seventh semester students from the undergraduate English program. The data collection techniques used included observations, document analysis, interviews, and a Preliminary English Test for students. The results were analyzed taking into account issues in discourse analysis and systemic functional linguistics. Results show reasons why students find it difficult to successfully complete the analysis of written texts. These results can serve as useful alternatives for planning reading lessons.Este artículo presenta un estudio de caso que busca analizar qué actividades, aspectos metodológicos y textuales causan dificultades en los estudiantes para analizar de manera crítica información en un curso de estrategias de lectura. Este estudio se realizó en la Universidad de Córdoba (Colombia) con estudiantes de séptimo semestre del programa de inglés. Las técnicas de recolección usadas fueron observaciones, análisis de documentos, entrevistas y un examen de competencia en inglés. Los resultados fueron analizados teniendo en cuenta elementos relevantes del análisis del discurso y de la lingüística sistémica. Los resultados mostraron las posibles razones por las cuales los estudiantes muestran dificultades para analizar textos escritos. Estos resultados pueden servir como alternativas para la planeación de clases de lectura.